Influenza B Virus Requires BM2 Protein for Replication - Hatta, Masato (American Society for Microbiology, 2004)
The BM2 protein of influenza B virus functions as an ion channel, which is suggested to be important for virus uncoating in endosomes of virus-infected cells. Because direct support for this function is lacking, whether BM2 plays an essential role in the viral life cycle remains unknown. We therefore attempted to generate BM2 knockout viruses by reverse genetics. Mutant viruses possessing M segments with the mutated initiation codon of BM2 protein at the stop-start pentanucleotide were viable and still expressed BM2. The introduction of multiple stop codons and a one-nucleotide deletion downstream of the stop-start pentanucleotide, in addition to disablement of the BM2 initiation codon, failed to generate viable mutant viruses, but the mutant M segments still expressed proteins that reacted with the BM2 peptide antiserum. To completely abolish BM2 expression, we generated a mutant M gene whose BM2 open reading frame was deleted. Although this mutant was not able to replicate in normal MDCK cells, it did replicate in a cell line that we established which constitutively expresses BM2. Furthermore, a virus possessing the mutant M gene lacking the BM2 open reading frame and a mutant NA gene containing the BM2 open reading frame instead of the NA open reading frame underwent multiple cycles of replication in MDCK cells, with exogenous sialidase used to supplement the deleted viral sialidase activity. These findings demonstrate that the BM2 protein is essential for influenza B virus replication.